Fatigue crack growth in full-scale railway axles – Influence of secondary stresses and load sequence effects. (March 2020) - Rieger, Martin; Moser, Christian; Brunnhofer, Peter; Simunek, David; Weber, Franz-Josef; Deisl, Andreas; Gänser, Hans-Peter; Pippan, Reinhard; Enzinger, Norbert
Highlights: Crack propagation tests on railway axles with variable load sequences. Real time crack growth measurement during fatigue tests. Residual stress measurement during crack propagation. Influence of residual stresses on residual lifetime. Abstract: A wheel-set axle is located in the unsprung part of a rail vehicle and takes a supporting role in the running gear. If the wheel-set axle fails, the train will inevitably derail. Depending on the time of failure, this can lead to catastrophic consequences. For this reason, a wheel-set axle is a highly safety-critical component of railway vehicles. Detailed knowledge of crack propagation in wheel-set axles is therefore of great importance for a modern safety concept. To analyse the material behaviour under external loads approximated from operating conditions, experimental investigations were carried out on 1:1 specimens. This article presents the results of these experimental investigations carried out within the framework of the research project "Eisenbahnfahrwerke 3 (EBFW 3)" – "Probabilistic Fracture Mechanical Concept for the Assessment of Railway Wheel-sets".